Advances in Studies on Microbiota Involved in Nitrogen Removal Processes and Their Applications in Wastewater Treatment - Mai, Wenning; Chen, Jiamin; Liu, Hai; Liang, Jiawei; Tang, Jinfeng; Wei, Yongjun (Frontiers in Microbiology, 2021)
The discharge of excess nitrogenous pollutants in rivers or other water bodies often leads to serious ecological problems and results in the collapse of aquatic ecosystems. Nitrogenous pollutants are often derived from the inefficient treatment of industrial wastewater. The biological treatment of industrial wastewater for the removal of nitrogen pollution is a green and efficient strategy. In the initial stage of the nitrogen removal process, the nitrogenous pollutants are converted to ammonia. Traditionally, nitrification and denitrification processes have been used for nitrogen removal in industrial wastewater; while currently, more efficient processes, such as simultaneous nitrification-denitrification, partial nitrification-anammox, and partial denitrification-anammox processes, are used. The microorganisms participating in nitrogen pollutant removal processes are diverse, but information about them is limited. In this review, we summarize the microbiota participating in nitrogen removal processes, their pathways, and associated functional genes. We have also discussed the design of efficient industrial wastewater treatment processes for the removal of nitrogenous pollutants and the application of microbiome engineering technology and synthetic biology strategies in the modulation of the nitrogen removal process. This review thus provides insights that would help in improving the efficiency of nitrogen pollutant removal from industrial wastewater.